In Situ Repair of 2D Chalcogenides under Electron Beam Irradiation. Issue 14 (16th February 2018) - Shen, Yuting; Xu, Tao; Tan, Xiaodong; He, Longbing; Yin, Kuibo; Wan, Neng; Sun, Litao
Abstract: Molybdenum disulfide (MoS2 ) and bismuth telluride (Bi2 Te3 ) are the two most common types of structures adopted by 2D chalcogenides. In view of their unique physical properties and structure, 2D chalcogenides have potential applications in various fields. However, the excellent properties of these 2D crystals depend critically on their crystal structures, where defects, cracks, holes, or even greater damage can be inevitably introduced during the preparation and transferring processes. Such defects adversely impact the performance of devices made from 2D chalcogenides and, hence, it is important to develop ways to intuitively and precisely repair these 2D crystals on the atomic scale, so as to realize high‐reliability devices from these structures. Here, an in situ study of the repair of the nanopores in MoS2 and Bi2 Te3 is carried out under electron beam irradiation by transmission electron microscopy. The experimental conditions allow visualization of the structural dynamics of MoS2 and Bi2 Te3 crystals with unprecedented resolution. Real‐time observation of the healing of defects at atomic resolution can potentially help to reproducibly fabricate and simultaneously image single‐crystalline free‐standing 2D chalcogenides. Thus, these findings demonstrate the viability of using an electron beam as an effective tool to precisely engineer materials to suit desired applications in the future. Abstract : Controlled electron‐beam irradiation can be utilized as a tool to repair nanopores in MoS2 and Bi2 Te3 and lead to high‐quality crystals with a low number of defects. The dynamic repair processes yield an in‐depth understanding of the repair mechanism in 2D chalcogenides: the sites with more surrounding atom columns have higher priority to be occupied by adatoms.